2023
DOI: 10.3389/fnut.2023.1235113
|View full text |Cite
|
Sign up to set email alerts
|

A pilot survey of selenium status and its geospatial variation among children and women in three rural districts of Zimbabwe

Abstract: IntroductionSelenium (Se) deficiency is increasingly recognized as a public health problem in sub-Saharan Africa.MethodsThe current cross-sectional study assessed the prevalence and geospatial patterns of Se deficiency among children aged 6–59 months (n = 741) and women of 15–49 years old (n = 831) selected by simple random sampling in rural Zimbabwe (Murewa, Shamva, and Mutasa districts). Venous blood samples were collected and stored according to World Health Organization guidelines. Plasma Se concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 55 publications
1
10
0
Order By: Relevance
“…The overall median (Q1, Q3) Se concentrations were 61.2 μg/L (48.7, 73.3) and 40.5 μg/L (31.3, 49.5) for children and women, respectively. Notable evidence of severe Se deficiency risk was observed in the sample population, with children recording plasma Se concentrations as low as 9.41 μg/L and 10.20 μg/L being the minimum in WRA ( 40 ). The urine and plasma samples were collected from individuals on the same day, allowing for comparison of urine and plasma at individual, household, EA, and district levels.…”
Section: Methodsmentioning
confidence: 89%
See 4 more Smart Citations
“…The overall median (Q1, Q3) Se concentrations were 61.2 μg/L (48.7, 73.3) and 40.5 μg/L (31.3, 49.5) for children and women, respectively. Notable evidence of severe Se deficiency risk was observed in the sample population, with children recording plasma Se concentrations as low as 9.41 μg/L and 10.20 μg/L being the minimum in WRA ( 40 ). The urine and plasma samples were collected from individuals on the same day, allowing for comparison of urine and plasma at individual, household, EA, and district levels.…”
Section: Methodsmentioning
confidence: 89%
“…The current study assesses the usefulness of casual urine Se concentration as an alternative biomarker to plasma Se concentration, which has previously been reported ( 40 ), for the population-level Se status. The plasma Se study found that Se deficiency is widespread among women and children in all three rural districts.…”
Section: Methodsmentioning
confidence: 93%
See 3 more Smart Citations